An introduction to infinite-dimensional differential geometry - Schmeding, A. (2022)
"This text introduces foundational concepts in infinite-dimensional differential geometry beyond Banach manifolds, exploring modern applications. Emphasising connections to finite-dimensional geometry, it is accessible to graduate students, as well as researchers wishing to learn about the subject. Also available as Open Access on Cambridge Core"--
Keywords: Infinite-dimensional manifolds; Geometry, Differential; MATHEMATICS / Topology